Blaze : [compact disc, unabridged] : a novel - Bachman, Richard (Simon & Schuster Audio, 2007)
Clayton Blaisell, Jr. was abused by his father. He in turn kidnaps a baby that is worth millions of dollars. Clayton becomes a crime partner with George who is killed and now haunts Clayton.